Unlocking the Path to Professional Teaching: Insights from Student Teachers and Mentor Teachers in an At-School Practicum Program - Sulisworo, Dwi; Lestari, Sri; Jatmika, Surya; Mustafa, Alim; Azizah, Nunung (The Indonesian Institute of Science and Technology Research, 2024)
This research aims to observe the implementation process of the Teacher Professional Program, specifically during the Practicum Experience in Schools (Program Praktik Lapangan or PPL), from the perspectives of the Mentor Teachers and the Student Teachers. The focus is on examining both groups' experiences and perceptions regarding the program's effectiveness and impact on teacher preparation and professional development. A qualitative research approach was applied, involving in-depth interviews with Mentor Teachers and Student Teachers and direct observation of the PPL process. The findings show that student teachers have developed competency in using various learning strategies while considering the learners' conditions and the learning objectives. They conducted a diagnostic test to assess the learning characteristics of their students and focused on developing several learning objectives, including critical thinking, science literacy, and communication skills. The student participants utilized various relevant information technologies, such as Physicslab, PhET Simulation, Octave, Canva, and Google Docs. The supervising teacher supported student teachers in managing the classroom from planning to evaluation, which is essential in providing a positive learning experience for student teachers and promoting their professional development. The observations showed that the students were comfortable with the student teachers and performed satisfactorily, which made the student teachers feel comfortable during their teaching practice. The support system from the supervising teacher is crucial in ensuring the effectiveness and impact of the program on teacher preparation and professional development.